PENGARUH PROMOSI DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI DAILYCIOUS CAFÉ RESTO KOTA BENGKULU - Yufiter, Habib; Islamuddin, Islamuddin (Yayasan Insani Mandiri Santani, 2024)
This research is a type of quantitative research. This research uses a purposive sampling technique. The data obtained in this research will be processed using SPSS 16 software. The model of this research is a multiple regression analysis research model. From the research results, it can be concluded that Promotion has a positive and significant effect on purchasing decisions at Dailycious Cafe Resto, Bengkulu City. Product innovation influences purchasing decisions at Dailycious Cafe Resto, Bengkulu City. Promotion and product innovation influence purchasing decisions at Dailycious Cafe Resto, Bengkulu City.Keywords: Promotion, Product Innovation, Purchasing Decisions.